Modelling of budget allocation for university library - Engku Abu Bakar, Engku Muhammad Nazri; Abdul Rahman, Syariza; Mohd Yusop, Noorezatty (Malaysia Institute of Statistics (ISM), Faculty of Computer and Mathematical Sciences, Universiti Teknologi MARA, 2011)
This paper suggests a simple approach to solve future budget allocation problems at Universiti Utara Malaysia’s library specifically, and with minor justification, all university libraries in general.The general objective of this suggestion is to help the library to allocate its annual budget efficiently whereby the acquisitions budget is distributed to all of its clients in a manner that considers a balance between continuing commitment and new initiatives, a balance between resources to support undergraduate learning and those to support graduate work and research, and a balance between subject disciplines.In order to achieve the goals, the suggested approach starts with the construction of a mathematical model to determine the total amount of its budget that should be allocated to each of its clients.Next, based on the budget allocated to each client, the approach continues with the construction of another mathematical model to determine the budget acquisition distribution for books and journals for each client.Upon determining the amount to be allocated for books and journals, the suggested approach ends with the construction of yet another mathematical model to identify the specific books and journals to be purchased for each client.